Theoretical Study of Indian Banking System - Ahmed Habeeb Khairullah; S Rosita (Journal of Social Commerce, 2022)
Banks play a significant part in India's financial system and contribute to economic growth. The banking industry is the foundation of every contemporary economy. It is one of the most significant foundations of the financial industry and plays a crucial role in economic performance. It is crucial for the growth of the nation's economy that financial demands be met; industry and agriculture demonstrate the greatest degree of dedication and accountability. Therefore, the growth of the nation is intimately tied to the growth of banks. Banks should not be seen as money changers in the contemporary economy, but as development leaders. In several economic sectors, they serve a crucial role in aggregating deposits and debt payments. The financial system reflects the country's economic life. Economic vitality is contingent upon the stability and efficacy of the financial system, which in turn is contingent upon a solid and sustainable banking system. A solid banking system that integrates deposits into productive sectors and a melting bank system allow the bank to fulfill its duties to investors. After India's independence, banks play a significant part in the country's social and economic growth. India is dominated by the banking industry, which accounts for more than half of the financial sector's assets. The Indian banking sector has seen a remarkable transformation due to the reforms of the financial industry, which are implemented in phases. In this context, the researcher has conducted an overview analysis of the Indian Banking System, resulting in the current paper.